GLP-1 Receptor Agonists and Cardiovascular Disease in Patients with Type 2 Diabetes - María Isabel del Olmo-Garcia; Juan Francisco Merino-Torres (Journal of Diabetes Research)
Diabetes mellitus is a chronic disease prevalence of which is high and continually growing. Cardiovascular disease continues to be the leading cause of death in patients with T2DM. The prevention of cardiovascular complications and the cardiovascular safety of treatments should be a primary objective when selecting treatment. Among all the drugs available, the compounds known as glucagon-like peptide-1 receptor agonists (GLP-1 RAs) appear to be not just innocuous in terms of CVD but indeed to be beneficial. GLP-1 RA actions not only translate on an improvement of well-known cardiovascular risk factors such as glycaemic control, dyslipidaemia, weight, or arterial hypertension but also might show benefits on endothelial function, coronary ischaemia, and heart failure. On the other hand, recent clinical trials aimed at studying cardiovascular episodes have been conducted with GLP-1 RAs. Only liraglutide and semaglutide have shown superiority in cardiovascular benefit compared with placebo. Although many of the mechanisms by which liraglutide and semaglutide produce a cardiovascular benefit are still unknown it would be desirable for these benefits to be incorporated into the therapeutic algorithms routinely used in clinical practice. The purpose of this review is to explore GLP-1 RA actions not only in cardiovascular risk factors (glucose, weight, and hypertension) but also the possible effects on established cardiovascular disease.